The perfect birth: a content analysis of midwives' posts about birth on Instagram - Anna Marsh; Vanora A. Hundley; Ann Luce; Yana Richens (BMC, 2023)
Abstract Background There is limited research into how midwives use social media within their professional role. Small pilot studies have explored the introduction of social media into maternity practice and teaching but there is little evidence around how midwives use social media professionally. This is important as 89% of pregnant women turn to social media for advice during pregnancy, and how midwives use social media could be influencing women, their perception of birth and their decision making. Methods Aim To analyse how popular midwives portray birth on the social media platform Instagram. This is an observational mixed methods study using content analysis. Five 'popular' midwives from each country (UK, New Zealand, USA and Australia) were identified and their posts about birth collated from a one-year period (2020-21). Images/videos were then coded. Descriptive statistics enabled comparison of the posts by country. Categorisation was used to analyse and understand the content. Results The study identified 917 posts from the 20 midwives' accounts, containing 1216 images/videos, with most coming from USA (n = 466), and UK (n = 239), Australia (n = 205) and New Zealand (n = 7) respectively. Images/videos were categorised into 'Birth Positivity', 'Humour', 'Education', 'Birth Story' and 'Advertisement'. Midwives' portrayals of birth represented a greater proportion of vaginal births, waterbirths and homebirths than known national birth statistics. The most popular midwives identified mainly had private businesses (n = 17). Both the midwives and women portrayed in images were primarily white, demonstrating a disproportionate representation. Conclusion There is a small midwifery presence on Instagram that is not representative of the broader profession, or the current picture of midwifery care. This paper is the first study to explore how midwives are using the popular social media platform Instagram to portray birth. It provides insight into how midwives post an un-medicalised, low risk representation of birth. Further research is recommended to explore midwives' motivation behind their posts, and how pregnant and postnatal women engage with social media.